Peluang, Tantangan, dan Strategi Peningkatan Literasi Wakaf di Kalangan Generasi Z: Opportunities, Challenges, and Strategies for Enhancing Waqf Literacy Among Z-Generation - Azwar, Azwar; Gunawan Baharuddin (Litera Academica Publishing, 2024)
This study aims to identify the challenges and opportunities in efforts to enhance waqf literacy among Generation Z, as well as to formulate effective and relevant strategies for improving waqf literacy within this demographic. The research employs a qualitative method with a descriptive-analytical approach. The findings reveal that although waqf literacy among Generation Z is still low, there are significant opportunities through the potential of Generation Z as drivers of waqf, their interest in social issues, openness to innovation and new technologies, support from educational institutions and communities, and their ability to collaborate and network. However, there are substantial challenges, including the low level of understanding of waqf among Generation Z, information gaps on digital platforms, the perception that waqf is only for the wealthy, a lack of application models that align with Generation Z’s lifestyle, and limited access and participation in waqf programs. Therefore, the strategies formulated must address these challenges while leveraging existing opportunities through educational campaigns on digital and social media, changing perceptions about waqf, using digital platforms to facilitate waqf participation, and collaborating with influencers and public figures. The implications of this research suggest that the right approach in conveying information and education about waqf can increase Generation Z’s participation in waqf activities, ultimately supporting the sustainability of waqf as a social financial instrument in the future.